Employees’ Perceptions of Performance Appraisal at BSI Bandar Lampung - Syaika Rona Aqilah; Wilda Saputri; Ani Setianingsih; Wella Eriska Ayu; Yudhinanto Yudhinanto (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to examine employees’ perceptions of performance appraisal at BSI Bandar Lampung, an institution in which appraisal practices play an important role in employee motivation and organizational development. A descriptive census approach was employed by involving all 90 employees, with data collected through a validated online questionnaire and analyzed using descriptive statistics. The research findings indicate that employees generally perceive the appraisal process as fair, transparent, and objective, with most respondents reporting satisfaction and motivation to enhance their career development. Nevertheless, some employees still experience limited transparency and report negative impacts on their well-being. This study contributes by providing empirical evidence from a public health higher education institution in Indonesia and highlighting the importance of strengthening communication, feedback, and attention to well-being in performance appraisal practices. The novelty of this research lies in its examination of employees’ perceptions within the context of a government-owned health polytechnic, offering insights to improve performance appraisal systems in similar public sector institutions. Keywords: Employee Perceptions; Performance Appraisal